Efficacy of the physiobiological parameter-based grading system for predicting the long-term prognosis after curative surgery for resectable pancreatic cancer. (March 2021) - Abe, Tomoyuki; Amano, Hironobu; Kobayashi, Tsuyoshi; Hattori, Minoru; Hanada, Keiji; Nakahara, Masahiro; Ohdan, Hideki; Noriyuki, Toshio
Abstract: Background: Several prognostic scoring systems based on cancer-related inflammation have been developed. We aimed to evaluate the efficacy of a novel physiobiological parameter-based grading system (PGS) for predicting the long-term prognosis after curative-intent surgery for pancreatic ductal adenocarcinoma. Methods: One-hundred fifty-nine consecutive patients with pancreatic ductal adenocarcinoma were enrolled. Univariate and multivariate analyses were performed to identify variables associated with overall survival and recurrence-free survival. Patients were stratified according to the PGS score with a cut-off value of 40.5 being estimated by receiver-operating characteristic curve analysis. Propensity score matching analysis (PSM) was performed to compare between patients with low and high scores in the physiobiological parameter-based grading system. Results: Univariate analysis showed that CEA elevation (p = 0.032), tumor size ≥20 mm (p < 0.001), lymph node metastasis (p < 0.001), high-PGS (p < 0.001), CA19-9 elevation (p < 0.001), Prognostic nutritious index (PNI) ≤40 (p = 0.002) and positive Glasgow prognostic score (GPS) (p = 0.001) were risk factors for poor overall survival. CEA elevation (p = 0.006), Tumor size ≥20 mm (p < 0.001), lymph node metastasis (p < 0.001), high-PGS (p < 0.001), CA19-9 elevation (p < 0.001), PNI ≤40 (p = 0.017) and positive GPS (p < 0.001) were identified as risk factors for poor recurrence-free survival. The multivariate analysis revealed that tumor size ≥20 mm (p = 0.007, p = 0.008, respectively) and high PGS score (p = 0.041, p = 0.018, respectively) were independently associated with poor overall survival and recurrence-free survival. Patients with high-PGS showed a significantly worse long-term prognosis even after PSM. Conclusion: The PGS is a novel nomogram that could effectively predict long-term outcomes following curative surgery in patients with pancreatic ductal adenocarcinoma.